Kidney Manifestations of Covid-19 - Abdul-Karim Olayinka Shitu; Daniel Gilbert Uchendu (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
Infection with the severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) virus causes the coronavirus disease 2019 (COVID-19). The disease is primarily a pulmonary disease but with multisystem (extra-pulmonary) manifestations, of which the kidneys are involved. Affection of the kidney is caused by the direct invasion of the virus or as a consequence of the immunological response to the presence of the virus. The resultant manifestation could range from an asymptomatic proteinuria to an acute kidney injury requiring kidney replacement therapy. The presence of kidney dysfunction in COVID-19 increases the severity of the disease and the risk of mortality.